Characterization of shear bond stress for design of composite slabs using an improved partial shear connection method - Abdullah, Redzuan; Kueh, Ahmad Beng Hong; Ibrahim, Izni S.; Easterling, W. Samuel (Journal of Civil Engineering and Management, 2015)
Eurocode 4 design provisions specify two methods for the design of composite slabs, namely the m-k and the partial shear connection (PSC) methods. Currently, the m-k method includes the concrete thickness and the shear span of the slab as variables while the PSC method does not. This has resulted in a better accuracy for the m-k method when slabs with varying dimensions are considered. It is demonstrated in this paper that the horizontal shear bond stress varies with the ratio of shear span to effective depth of slab, defined as the slenderness. To include such an effect, a linear shear bond-slenderness equation is proposed. Using the proposed relationship, a linear interpolation of shear bond strength based on two configurations, determined from the outcomes of the bending tests for compact and slender slabs, has been satisfactorily performed. The shear bond strength obtained from this interpolation can be used in collaboration with the existing PSC method, such that the accuracy of the prediction of the composite slab capacity can be considerably improved, the validity of which has been verified with published results from literatures.